A new genus and new species of leucosiid crab from New Caledonia,with a note on the validity of Tanaoa serenei (Richer de Forges, 1983) (Crustacea: Decapoda: Brachyura) - Ng, Peter K.l.; de Forges, Bertrand Richer (Zootaxa, 2007)
Randallia serenei Richer de Forges, 1983, is shown to be a distinct species and not a synonym of Tanaoa distinctus (Rathbun, 1894). Two other species currently placed in Randallia, R. granulata Miers, 1886, and R. speciosa Chen, 1989, are also transferred to Tanaoa Galil, 2003. A new genus and new species of leucosiid crab, Galilia narusei, is also described from New Caledonia. While superficially resembling species of Toru Galil, 2003, it differs markedly in its very granular carapace, rounded intestinal tubercles, short male chelipeds and ambulatory legs as well as a gently bent male first pleopod. The nomenclature of Randallia pustulilabris Alcock, 1896, is also discussed, and Ihleorandallia Števčić, 2005, a nomen nudum, is shown to be a junior synonym of Toru.